Data envelopment analysis in evaluating the technical and scale efficiencies of micro enterprises in Sabah - Muhammad Ameer Aiman Mohd Zulkifli; Jumat Sulaiman; Salmah Topimin; Siti Rahayu Mohd Hashim (Human Resource Management Academic Research Society, 2025)
This paper evaluates the performance of 26 micro enterprises in Sabah under the bakery sector using the Data Envelopment Analysis. The performance indicators which are the inputs and outputs for this study are chosen based on past studies. The Charnes, Cooper and Rhodes (CCR) Data Envelopment Analysis will give the Overall Technical Efficiency score whereas the Banker, Charnes and Cooper (BCC) Data Envelopment Analysis will reveal the Pure Technical Efficiency score for all micro enterprises. From there, the Scale Efficiency is obtained by finding the ratio of the relative efficiency score given by both CCR and BCC Data Envelopment Analysis. This paper also evaluates the inefficient micro enterprises in terms of the improvements in inputs and outputs to become more efficient as well as identifying which efficient micro enterprises will be used as a reference set for these inefficient micro enterprises to become more efficient.